Anthelmintic resistance in equine nematodes: Current status and emerging trends. (December 2022) - Nielsen, M.K.
Abstract: Anthelmintic resistance is reported in equine nematodes with increasing frequency in recent years, and no new anthelmintic classes have been introduced during the past 40 years. This manuscript reviews published literature describing anthelmintic resistance in cyathostomins, Parascaris spp., and Oxyuris equi with special emphasis on larvicidal efficacy against encysted cyathostomin larvae and strongylid egg reappearance periods (ERP). Resistance to benzimidazoles and pyrimidines is highly prevalent in cyathostomin populations around the world, and macrocyclic lactone resistance has been documented in cyathostomins in recent years as well. Two recent studies have documented resistance to the larvicidal regimen of fenbendazole, whereas the larvicidal efficacy of moxidectin is variable, but with no evidence of a reduction from historic levels. In the 1990s, ERP estimates were 8–10 and 12–16 weeks for ivermectin and moxidectin, respectively, while several studies published after year 2000 found ERPs to be 5 weeks for both compounds. This is a clear change in anthelmintic performance, but it remains unclear if this is due to development of anthelmintic resistance or selection for other biological traits leading to a quicker resumption of strongylid egg shedding following anthelmintic treatment. Macrocyclic lactone resistance is common in Parascaris spp. around the world, but recent reports suggests that resistance to the two other classes should be monitored as well. Finally, O. equi has been reported resistant to ivermectin and moxidectin in countries representing four continents. In conclusion, multi-drug resistance is becoming the norm in managed cyathostomin populations around the world, and a similar pattern may be emerging in Parascaris spp. More work is required to understand the mechanisms behind the shortened ERPs, and researchers and veterinarians around the world are encouraged to routinely monitor anthelmintic efficacy against equine nematodes. Graphical abstract: Image 1 Highlights: Cyathostomins are widely resistant to pyrimidines and benzimidazoles. Cyathostomins have been reported resistant to macrocyclic lactones in recent years. The interpretation of shortened egg reappearance periods is not clear. Parascaris spp. are widely resistant to macrocyclic lactones. Oxyuris equi has been documented resistant to macrocyclic lactones.